The Art of Selling Your Business - Warrillow, John (Ascent Audio, 2021)
Punch Above Your Weight Class When Selling Your Business Every owner must part with their business one day. Many will close their doors, realizing little for their life's work-while a select few will become fabulously wealthy. The Art of Selling Your Business: Winning Strategies & Secret Hacks for Exiting on Top is the last in a trilogy of books by author John Warrillow on building value. The first, Built to Sell, encouraged small business owners to begin thinking about their business as more than just a job. The Automatic Customer tagged recurring revenue as the core element in a valuable company and provided a blueprint for transforming almost any business into one with an ongoing annuity stream. Warrillow completes the set with The Art of Selling Your Business. This essential guide to monetizing a business is based on interviews the author conducted on his podcast, Built to Sell Radio, with hundreds of successfully cashed-out founders.